DC-DC converter-in-package design - Tay, Sun Yang (Nanyang Technological University, 2020)
An on-chip inductor is proposed for the application of designing a fully integrated DCDC converter. It is designed by stitching gold bond wires onto aluminium metal strip fabricated on the CMOS top metal layer level to form multiturn current loops. Both materials have very low resistance which results in an on-chip inductor with high quality factor. The proposed on-chip inductor design combines both solenoid and toroidal structures to form a new on-chip square toroidal inductor which have high inductance, high quality factor and low magnetic flux leakage. The on-chip square toroidal inductor is modelled and simulated with High Frequency Structure Simulator (HFSS) by Ansoft. The inductor occupies an area of 2 mm2 and the simulation result shows that the inductor has an inductance of 52nH, a quality factor of 8.02 and a total series resistance of 4.08Ω at 100MHz.